Cave and worship in Ancient Greece : new approaches to landscape and ritual - Katsarou, Stella; Nagel, Alexander (Abingdon : Routledge, 2021)
Cave and Worship in Ancient Greece brings together a series of stimulating chapters contributing to the archaeology and our modern understanding of the character and importance of cave sanctuaries in the fi rst millennium BCE Mediterranean. Written by emerging and established archaeologists and researchers, the book employs a fascinating and wide range of approaches and methodologies to investigate, and interpret material assemblages from cave shrines, many of which are introduced here for the fi rst time. An introductory section explores the emergence and growth of caves as centres of cult and religion. The chapters then probe some of the meanings attached to cave spaces and votive materials such as terracotta fi gurines, and ceramics, and those who created and used them. The authors use sensory and gender approaches, discuss the identity of the worshippers, and the contribution of statistical analysis to the role of votive materials. At the heart of the volume is the examination of cave materials excavated on the Cycladic islands and Crete, in Attika and Aitoloakarnania, on the Ionian islands and in southern Italy. This is a welcome volume for students of prehistoric and classical archaeology,enthusiasts of the history of caves, religion, ancient history, and anthropology.
Introduction: On Reading Caves and Ancient Greek CultStella Katsarou and Alexander NagelThe Dawn of Ancient Greek Cave Cult: Prehistoric Cave SanctuariesStella KatsarouCaves as Sites of Sensory and Cognitive Enhancement: The Idaean Cave on Crete NassosPapalexandrouCaves and Consumption:The Case of Polis Bay, IthacaCatherine Morgan and Chris HaywardCommunities, Consumption and a Cave: The Profile of CultatDrakainaCave onKephalloniaAgathi KaradimaA River Ran Through It: Circulating Images of Ritual and Engaging Communities in a Cave in AitoloakarnaniaAlexander NagelThe Cave of Pan at Marathon, Attica:New Evidence for thePerformance of Cult in the Historic Era Jorge J. Bravo III and Alexandra MariThe Face of Cave Rituals: Terracotta Figurines in Greek Sacred CavesKatja Sporn Approaching Cult and Ritual in CycladicCaves Erica AnglikerGrottoes and the Construction of Cult in Southern Italy Rebecca Miller Ammerman
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Cave temples -- Greece -- History; Greece -- Antiquities